Liquid-phase approach to glass-microfiber-reinforced sulfide solid electrolytes for all-solid-state batteries - El-Shinawi, H; Darnbrough, E; Perera, J; McClelland, I; Armstrong, DEJ; Cussen, EJ; Cussen, SA (American Chemical Society, 2023)
Deformable, fast-ion conducting sulfides enable the construction of bulk-type solid-state batteries that can compete with current Li-ion batteries in terms of energy density and scalability. One approach to optimizing the energy density of these cells is to minimize the size of the electrolyte layer by integrating the solid electrolyte in thin membranes. However, additive-free thin membranes, as well as many membranes based on preprepared scaffolds, are difficult to prepare or integrate in solid cells on a large scale. Here, we propose a scalable solution-based approach to produce bulk-type glass-microfiber-reinforced composites that restore the deformability of sulfide electrolytes and can easily be shaped into thin membranes by cold pressing. This approach supports both the ease of preparation and enhancement of the energy density of sulfide-based solid-state batteries.